2017
DOI: 10.1089/gg.2017.0011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genetics and Gender in Takotsubo Syndrome: Unexplored Areas of an Incompletely Understood Disease

Abstract: Stress cardiomyopathy, also known as ''Takotsubo syndrome'' (TS), is a complex disease that typically affects postmenopausal women. The pathophysiology is still largely unknown, but evidence of a frequent association between TS and stressful events has evoked the hypothesis of a pathophysiologic role of sympathetic overdrive in the myocardial dysfunction. However, despite several studies, the role gender plays in TS onset remains unclear because stress cardiomyopathy also has been described in young women and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In SCAD, genomewide association studies have identified genetic risk variants, however studies have been small and results conflicting (24). In takotsubo syndrome, reports of familial cases, high recurrence rates and case reports of patients with rare genetic syndromes supports a familial component (25)(26)(27). The lack of evidence of a family history of a MINOCA in our study is not proof of absence of a family history of MINOCA but could be a result of limitations in the study design, including sample size and selection.…”
Section: Familial Risk Of Minocamentioning
confidence: 99%
“…In SCAD, genomewide association studies have identified genetic risk variants, however studies have been small and results conflicting (24). In takotsubo syndrome, reports of familial cases, high recurrence rates and case reports of patients with rare genetic syndromes supports a familial component (25)(26)(27). The lack of evidence of a family history of a MINOCA in our study is not proof of absence of a family history of MINOCA but could be a result of limitations in the study design, including sample size and selection.…”
Section: Familial Risk Of Minocamentioning
confidence: 99%